1991
DOI: 10.1128/jvi.65.6.3151-3160.1991
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-early gene expression is sufficient for induction of natural killer cell-mediated lysis of herpes simplex virus type 1-infected fibroblasts

Abstract: Herpes simplex virus type 1 (HSV-1)-infected human fibroblast (HSV-FS) targets are susceptible to lysis by natural killer (NK) cells, whereas uninfected FS are resistant to lysis. Studies were undertaken to determine the mechanism of this preferential susceptibility. HSV-FS were not intrinsically less stable than FS, as determined by a 5"Cr release assay under hypotonic shock in the presence of rat granule cytolysin and by sensitivity to anti-human leukocyte antigen class I antibody plus complement. Single-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 34 publications
(31 reference statements)
3
8
0
Order By: Relevance
“…In turn, monocytes may produce TNF-a to enhance NK cell killing of HSV-infected cells in inflamed tissue. 54 MICA, which was up-regulated on Toll-like receptor-stimulated monocytes, 55 was not induced by HSV-1, consistent with a study in which MICA in infected cells was down-regulated by late HSV-1 gene products. 56 Immediate early gene expression was found to be sufficient for NK cell-mediated lysis of HSV-infected fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In turn, monocytes may produce TNF-a to enhance NK cell killing of HSV-infected cells in inflamed tissue. 54 MICA, which was up-regulated on Toll-like receptor-stimulated monocytes, 55 was not induced by HSV-1, consistent with a study in which MICA in infected cells was down-regulated by late HSV-1 gene products. 56 Immediate early gene expression was found to be sufficient for NK cell-mediated lysis of HSV-infected fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
“…56 Immediate early gene expression was found to be sufficient for NK cell-mediated lysis of HSV-infected fibroblasts. 54 Follow-up studies found that the HSV-1 immediate early protein ICP0 induced lysis of HSV-infected cells via the natural cytotoxicity receptors. 57 Yet, the induced molecules on target cells were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…The infectious, but replication‐incompetent HSV‐1 d 106S still expresses the immediate early proteins ICP0 and ICP6 . Expression of ICP0 by infected cells was sufficient for recognition of NK cells by natural cytotoxicity receptors . After UV irradiation, viral DNA is cross‐linked and the virus no longer expresses immediate early proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Aborted viral replication, at stages prior to host cell destruction, is sufficient to obtain an effective immune response against HSV-I. Moreover, limited HSV-1 replication is superior to exposure of the immune system to purified viral proteins (Chan et al 1989, McDermott et al 1989, Fitzgerald-Bocarsly et al 1991. Indeed, immediate early gene expression is sufficient to induce a natural killer cell-mediated immunity (Fitzgerald-Bocarsly et al 1991), while ultraviolet light or heat inactivation of virus reduces the ability to form HSV-specific cytotoxic T lymphocytes (Lawman et al 1980).…”
Section: Hsv-1mentioning
confidence: 99%
“…Moreover, limited HSV-1 replication is superior to exposure of the immune system to purified viral proteins (Chan et al 1989, McDermott et al 1989, Fitzgerald-Bocarsly et al 1991. Indeed, immediate early gene expression is sufficient to induce a natural killer cell-mediated immunity (Fitzgerald-Bocarsly et al 1991), while ultraviolet light or heat inactivation of virus reduces the ability to form HSV-specific cytotoxic T lymphocytes (Lawman et al 1980). Likewise, infection of experimental animals with viral mutants that have an aborted replication cycle protects them from the development of encephalitis and keratitis (Nguyen et al 1992, Morrison & Knipe 1994.…”
Section: Hsv-1mentioning
confidence: 99%